Factors Influencing Biogenic Amines Accumulation in Dairy Products - Linares, Daniel M.; del Río, Beatriz; Ladero, Victor; Martínez, Noelia; Fernández, María; Martín, María Cruz; Alvarez, Miguel A. (Frontiers in Microbiology, 2012)
Fermented foods are within the food products more often complained of having caused biogenic amines poisoning. Concerning milk-based fermented foods, cheese is the main product likely to contain significant levels of biogenic amines, specially tyramine, histamine and putrescine. Prompted by the increasing awareness of the risks related to dietary uptake of high biogenic amine loads, in this review we report about cheese elaboration and processing technological aspects affecting biogenic amines levels. Synthesis of biogenic amines is possible only when three conditions converge: i) availability of the substrate amino acids; ii) presence of microorganisms with the appropriate catabolic pathway activated; and iii) environmental conditions favorable to the decarboxilation activity. These conditions depend on several factors such as milk treatment (pasteurization), use of starter cultures, NaCl concentration, time and temperature of ripening and preservation, pH… which will be discussed in this chapter.